Sudakov evolution without unitarity - J. Altmann; H. T. Li; L. Scyboz; P. Skands (European Physical Journal C: Particles and Fields)
Abstract We present a method for sampling singular functions defined on (nested) multiparticle phase spaces, based on a generalisation of parton-shower phase-space generation techniques. At the heart of the method are three key ingredients: (1) the Sudakov sampling by which shower-style calculations sweep across phase space in an ordered manner, from hard to soft; (2) the sequential nesting of multiparticle phase spaces; and (3) the factorisations obeyed by singular multiparton amplitudes on the edges of these phase spaces. We demonstrate a C++ implementation of the proposed algorithm, dubbed Sunshine (loosely derived from Sudakov Nesting of Hard Integrals), for hadronic Z decays, and use it to test the tree-level accuracy of the Vincia sector shower through $$\mathcal{O}(α _s^2)$$ O ( α s 2 ) . Graphic Abstract